Colocutaneous Fistula Complicating Therapeutic Mesenteric Embolisation - Camprodon, Ram (The Royal College of Surgeons of England, 2007)
Percutaneous embolotherapy has now assumed an important role in the management of massive colonic haemorrhage. However, this therapeutic option is associated with a significant risk of irreversible segmental colonic ischaemia. We present a case where distal segmental ischaemia led to a colocutaneous fistula, a complication not reported so far in the literature.